Analysis of low‐frequency current ripple transmission in series‐resonant LED drivers. Issue 9 (1st April 2015) - de Melo, M.F.; Vizzotto, W.D.; Chies, L.; Dalla Costa, M.A.; Alonso, J.M.
Abstract : The use of series‐resonant converters (SRCs) in light‐emitting diode (LED) drivers has increased due to its simplicity and high efficiency. Furthermore, the use of a SRC provides reduction of the low‐frequency ripple in the LED current, originated by the bus voltage ripple. Thus, an analysis of the SRC aiming to define a design methodology to improve the current ripple reduction provided by the SRC is proposed. Moreover, a discussion about the main factors that have influenced ripple reduction and the limits for this attenuation is presented, which have not been explored in the literature hither to.